Pamela in her exalted condition - Richardson, Samuel 1689-1761 (Cambridge University Press, 2012)
Pamela in Her Exalted Condition follows the heroine of Richardson's hugely popular first novel into married life. In the process, he explores both the experience of women beyond the stage of courtship and provides a fascinating insight into the social and cultural life of the mid eighteenth century. The first ever scholarly edition of the novel, this volume features a critically edited text, general and textual introductions, full annotations and textual apparatus. Appendices describe all the editions published in Richardson's lifetime as well as early nineteenth-century editions. The original illustrations from the popular octavo edition of 1742 and Richardson's index are reproduced. The publication of this novel in the Cambridge edition allows the sequel to Pamela to take its rightful place in the critical study of Richardson's development as a novelist